2017
DOI: 10.1089/scd.2017.0071
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cellular Proliferation in Adipogenic Differentiation of Human Adipose Tissue-Derived Mesenchymal Stem Cells

Abstract: Mitotic clonal expansion has been suggested as a prerequisite for adipogenesis in murine preadipocytes, but the precise role of cell proliferation during human adipogenesis is unclear. Using adipose tissue-derived human mesenchymal stem cells as an in vitro cell model for adipogenic study, a group of cell cycle regulators, including Cdk1 and CCND1, were found to be downregulated as early as 24 h after adipogenic initiation and consistently, cell proliferation activity was restricted to the first 48 h of adipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 52 publications
2
44
1
2
Order By: Relevance
“…Besides, these two markers have been found to be involved in growth arrest of differentiation [ 30 , 31 ]. Before preadipocyte differentiation, growth arrest is a necessary process for blocking the cell in the G 1 phase [ 32 , 33 ]; restricted cell proliferation has been found to appear at D2 of differentiation in human mesenchymal stem cells [ 32 , 34 ]. In the G 1 /S phase, CDK1 , CCND1 , and E2F1 have been shown to play a key role in regulating the cell cycle [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, these two markers have been found to be involved in growth arrest of differentiation [ 30 , 31 ]. Before preadipocyte differentiation, growth arrest is a necessary process for blocking the cell in the G 1 phase [ 32 , 33 ]; restricted cell proliferation has been found to appear at D2 of differentiation in human mesenchymal stem cells [ 32 , 34 ]. In the G 1 /S phase, CDK1 , CCND1 , and E2F1 have been shown to play a key role in regulating the cell cycle [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the G 1 /S phase, CDK1 , CCND1 , and E2F1 have been shown to play a key role in regulating the cell cycle [ 35 ]. Furthermore, the expression of CDK1 and CCND1 decreased at the early stage of differentiation in human and porcine preadipocytes [ 34 , 36 ]. Additionally, PPARG has been reported to control the cell cycle by decreasing the activity of E2F and CCND1 and upregulating the expression of cyclin-dependent kinase inhibitors [ 30 , 37 , 38 ], while CEBPA can repress the expression of E2F1 , which results in the impairment of the ability of cell differentiation, and simultaneously suppresses cell proliferation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The culture medium was replaced with fibroblast-inducing medium containing 20 ng/ml bFGF (Gibco) and 20 ng/ml EGF (Gibco), and then ADSCs were cultured to 40–50% confluence. [ 15 16 ] Cells were cultured for another 2 weeks, and the medium was changed every 2–3 days. The cells were then identified by flow cytometry and immunohistochemistry.…”
Section: Ethodsmentioning
confidence: 99%
“…Besides, previous studies also showed that the downregulation of CDK1 was related to osteogenic differentiation disorder and senescence of MSCs [22][23][24]. In addition, it was interesting that expression knockdown of CDK1 resulted in significantly increased adipogenic differentiation of AD-MSCs [25]. Therefore, abnormal expression of CDK1 in MSCs may also result in dysfunction of MSCs and lead to progression of MM although further functional studies are still needed.…”
Section: Discussionmentioning
confidence: 99%